Consumer’s Intention to use a Cashless payment application in Thailand - Dinesh Elango; Sutida Pimpin (Journal of Research and Multidisciplinary, 2020)
This empirical study is about the factors that influence the consumers’ intention to use a cashless payment application supported by a number of hypotheses and it's influence on the intention to use. The results present the influence between variables (1) price, (2) usefulness, (3) responsiveness, (4) ease of use, (5) security and trust. The effect of trust and security has long been recognized in online transaction literature. This study has developed a conceptual model to support the factors which have an influence on consumers’ intention to use cashless payment. The required data were gathered from a sample of 393 respondents who are living in Bangkok, the factors that influence on the intention to use the cashless payment application have four variables and have two variable is not the main factors that consumers’ concerned. The goal is to find the benefit for Thai people and the service provider in order to improve the service or create new functions to influence the consumer’s intention.